2019
DOI: 10.1111/jgh.14616
|View full text |Cite
|
Sign up to set email alerts
|

Superior clinical outcomes of peroral endoscopic myotomy compared with balloon dilation in all achalasia subtypes

Abstract: Background and Aim Optimal treatment modalities for each of the three subtypes of achalasia are still under debate. Differences in prognosis and long‐term outcomes between peroral endoscopic myotomy (POEM) and balloon dilation (BD) are also unclear. We aimed to compare the treatment outcomes of BD and POEM in each subtype of achalasia by using information from the manometry database of a tertiary referral center in Korea. Methods Data from 5207 esophageal manometry procedures performed between 1989 and 2016 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…A recent comparative study identified 64 and 177 patients who underwent POEM and PD, respectively. At the 24 months follow-up period, the clinical success rate of POEM was much higher than PD across all subtypes, although only type I and type II were statistically significant (type 1: 92.0% vs. 51.1%, P=0.004; type 2: 92.3% vs. 59.8%, P=0.007; and type 3: 91.7% vs. 55.6%, P=0.051) (58). A recent meta-analysis comparing outcomes of treatment for achalasia for all manometric subtypes, evaluated 1,575 patients and found that POEM was more likely to be successful than LHM for both type I (OR, 2.97; 95% CI, 1.09 to 8.03; P=0.032) and type III (OR, 3.50; 95% CI, 1.39 to 8.77; P=0.007) achalasia.…”
Section: Poem Compared To Lhm and Pd For Achalasiamentioning
confidence: 89%
“…A recent comparative study identified 64 and 177 patients who underwent POEM and PD, respectively. At the 24 months follow-up period, the clinical success rate of POEM was much higher than PD across all subtypes, although only type I and type II were statistically significant (type 1: 92.0% vs. 51.1%, P=0.004; type 2: 92.3% vs. 59.8%, P=0.007; and type 3: 91.7% vs. 55.6%, P=0.051) (58). A recent meta-analysis comparing outcomes of treatment for achalasia for all manometric subtypes, evaluated 1,575 patients and found that POEM was more likely to be successful than LHM for both type I (OR, 2.97; 95% CI, 1.09 to 8.03; P=0.032) and type III (OR, 3.50; 95% CI, 1.39 to 8.77; P=0.007) achalasia.…”
Section: Poem Compared To Lhm and Pd For Achalasiamentioning
confidence: 89%
“…In a recent retrospective study, POEM appears to be more effective than PD after 2 years of treatment in patients with all manometric subtypes of achalasia, but the incidence of postprocedure reflux remains a concern. 16 Similarly, a systematic review of postprocedure GERD after POEM compared with LHM reported significantly more reflux symptoms (19.0% versus 8.8%), abnormal acid exposure (39.0% versus 16.8%), and esophagitis (29.4% versus 7.6%) after POEM. 17 Selecting a treatment option Although endoscopic BTI is an established treatment modality for achalasia, a meta-analysis comparing BTI with both single PD and HM showed BTI to be less durable than both.…”
Section: Esophagealmentioning
confidence: 92%
“…The efficacy of POEM vs PD was 92% vs 51% in type I (P = 0.004), 92.3% vs 59.8% in type II (P = 0.007), and 91.7% vs 55.6% (P = 0.051) in type III achalasia. 76 In a multi-center randomized trial comparing POEM with PD, treatment success was achieved in 92% of patients in POEM group as compared to 54% of patients in the PD group at twoyears follow-up. On the other hand, reflux esophagitis was significantly more frequent after POEM as compared to PD (41% vs 7%).…”
Section: Poem and Gastroesophageal Refluxmentioning
confidence: 99%